2014
DOI: 10.1017/jgc.2014.16
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic Victimisation on Emotional and Behavioural Difficulties of Adolescents

Abstract: The current study used developmental trajectories to examine the relationship between internalising and externalising behaviours and victimisation over the transition period from primary to secondary school. Data were collected using a self-completion questionnaire four times over 3 years from 3,459 students aged 11-14 years. Students were tracked longitudinally to assess their knowledge, attitudes, mental health and bullying experiences during the transition period. Multilevel modelling was used to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Improved communication between parents and adolescents and decreased bullying victimization explained why emotional well-being remained stable between 2013 and 2017, despite a further increase in schoolwork pressure. Lester and Cross (2014) found that men who had been victimized in school had worse well-being and presented behavioral and hyperactivity problems, whereas women who had been victimized by peers also had decreased well-being, presenting emotional symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Improved communication between parents and adolescents and decreased bullying victimization explained why emotional well-being remained stable between 2013 and 2017, despite a further increase in schoolwork pressure. Lester and Cross (2014) found that men who had been victimized in school had worse well-being and presented behavioral and hyperactivity problems, whereas women who had been victimized by peers also had decreased well-being, presenting emotional symptoms.…”
Section: Introductionmentioning
confidence: 99%